Stress and stressors of medical student near-peer tutors during courses: a psychophysiological mixed methods study - Hundertmark, Jan; Alvarez, Simone; Loukanova, Svetla; Schultz, Jobst-Hendrik (BMC medical education, 2019)
Structured peer-led tutorial courses are widespread and indispensable teaching methods that relieve teaching staff and contribute to the development of students’ competencies. Nevertheless, despite high general stress levels in medical students and associated increases in psychopathology, specific knowledge of peer tutors’ additional burdens is very limited.
Gesehen am 23.05.2019